1968
DOI: 10.1016/0026-0495(68)90038-3
|View full text |Cite
|
Sign up to set email alerts
|

A diabetogenic polypeptide from hog and sheep adenohypophysis similar to that found in lipoatrophic diabetes

Abstract: A polypeptide possessing physical and biological properties similar to that excreted in the urine by patients with lipoatrophic diabetes was previously isolated from bovine adenohypophysis. A similar principle has now been obtained from the anterior lobes of hog and sheep pituitaries by the same procedures of isolation. The material from these animals also induces hyperglycemia and insulin resistance both in humans and dogs. The substance exhibits no similarity in physicochemical properties to either growth ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1970
1970
1980
1980

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…A hypothalamic disturbance is considered pathogenetic in lipoatrophic diabetes, in both the congenital and acquired forms (1,6,22,24,26). Via abnormal neurohumoral signals a loss of fat in the subcutis and internal depots is induced concomitant with insulin resistance (1,21,24,29). How these signals act in detail is not known, but in both animal experiments and clinical studies, urinary peptides have been found with adipo- kinetic, diabetogenic and anti-insulin properties (7,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypothalamic disturbance is considered pathogenetic in lipoatrophic diabetes, in both the congenital and acquired forms (1,6,22,24,26). Via abnormal neurohumoral signals a loss of fat in the subcutis and internal depots is induced concomitant with insulin resistance (1,21,24,29). How these signals act in detail is not known, but in both animal experiments and clinical studies, urinary peptides have been found with adipo- kinetic, diabetogenic and anti-insulin properties (7,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The condition is associated with hypothalamic dysfunction. It is thought that both abnormal humoral and neural stimuli may induce insulin resistance and loss of fat depots (1,6,7,20,21,22,24,26,29).…”
Section: Abstract: C-peptide Lipoatrophic Diabetes Urinary Polypepmentioning
confidence: 99%
“…The effects of insulin and of the diabetogenic peptide on glycogen synthase activation (Table 2) were then evaluated on 4 and 5. 0.04 jug/ml of insulin = 1 mU/ml; 0.2 Ag/ml of insulin = 5 mU/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence also suggests that this peptide is not adrenocorticotrophic hormone (3) or prolactin (4). Therefore, the suggestion has been made that this is a novel pituitary peptide (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation